Success Factors of Implementing Quality Assurance System in Public Algerian Universities from the View Point of Quality Assurance Officials - Saliha Reggad (University of Science and Technology, Yemen, 2017)
This study aimed to examine the success factors of implementing quality assurance system in public Algerian universities from the view point of quality assurance officials. To achieve this aim,  a questionnaire, as a measurement tool, was used , after verifying its psychometric properties. The study showed differences  in the quality assurance officials' points of view concerning the appropriate policy of implementing the Quality Assurance System.   The results also revealed the participants' approval of the majority of success factors which are considered as the basic potentials of implementing the quality assurance system very effectively. The most important factors are: stakeholders' awareness-raising of quality culture; senior management support for the process of implementing quality assurance system; the need to bring a change in the strategic orientation of the institution in terms of its vision, mission and objectives;  supporting the establishment of effective information systems; and changing common misconceptions so as to be in line with the values required for the successful implementation of the system, and the adoption of adequate incentive system. Keywords: Quality assurance, Quality assurance system, Success factors, Public Algerian universities.